Bahasa Inggris - Putri, Erika Emilia; Silviani, Ninne Zahara; Tantimin, Tantimin (Uti Possidetis: Journal of International Law, 2025)
Background: This study discusses the regulation and mechanism for the return of assets resulting from corruption crimes through international cooperation in the form of Mutual Legal Assistance (MLA) by comparing the practice in Indonesia and Singapore.Methodology: This study uses normative research methods and data collection techniques through literature review with secondary data sources and using statute and comparative approaches. Objectives: The study aims to compare the asset recovery practices through MLA in Indonesia and Singapore. Findings: The findings of this study reveal that Indonesia is still standing on a relatively suboptimal rate of return on assets resulting from corruption compared to Singapore. And, although Indonesia is a party of the ASEAN MLA, Indonesia also implements the bilateral agreements with countries inside and outside ASEAN. Originality/Novelty:The results of this study show that Indonesia needs to strengthen its diplomacy ties with the other countries, pass the Asset Forfeiture Bill, and make the ASEAN MLA as its main agreement to implement an efficient asset returns in the ASEAN region.